2015
DOI: 10.1108/sr-03-2014-626
|View full text |Cite
|
Sign up to set email alerts
|

Complex conductivity reconstruction in multiple frequency electrical impedance tomography for fabric-based pressure sensor

Abstract: Purpose – The aim of this paper is to introduce and to evaluate the performance of a multiple frequency complex impedance reconstruction for fabric-based EIT pressure sensor. Pressure mapping is an important and challenging area of modern sensing technology. It has many applications in areas such as artificial skins in Robotics and pressure monitoring on soft tissue in biomechanics. Fabric-based sensors are being developed in conjunction with electrical impedance tomography (EIT) for pressure m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 11 publications
(15 reference statements)
0
9
0
Order By: Relevance
“…The pressure sensor was made using Veloster material which acts as a semi-permeable layer between two pieces of conductive fabric to create pressure on it (Yang et al, 2015). After experimentation, it was observed that the response to pressure was not steady using Veloster (Randhawa et al, 2018).…”
Section: Hardware Descriptionmentioning
confidence: 99%
“…The pressure sensor was made using Veloster material which acts as a semi-permeable layer between two pieces of conductive fabric to create pressure on it (Yang et al, 2015). After experimentation, it was observed that the response to pressure was not steady using Veloster (Randhawa et al, 2018).…”
Section: Hardware Descriptionmentioning
confidence: 99%
“…where α is the regularization parameter, and I is the identity matrix. 23 Here, the sensitivity method was adopted to compute J. 24 Each term of J (i.e., Jlkn), which is the derivative of the measured boundary voltage with respect to the conductivity of each finite element voxel, is evaluated using (5):…”
Section: B Inverse Problemmentioning
confidence: 99%
“…where α is the regularization parameter, and I is the identity matrix. 23 Here, the sensitivity method was adopted to compute J . 24 Each term of J (i.e.…”
Section: Eit Backgroundmentioning
confidence: 99%
“…Stretchable conductive materials incorporated with electrical impedance tomography (EIT) can be an alternative solution to overcome aforementioned limitations4243444546474849505152. Electrical impedance tomography is a technique that computes internal conductivity distribution from continuum conductive model using electrodes fabricated along the boundary of the conductive material53.…”
mentioning
confidence: 99%
“…Here, the electrodes are used to apply electrical currents and to measure electrical potentials. This technique has been used to demonstrate a stretchable and sensitive electronic skin covering on three dimensional contoured surfaces without any internal wiring using conductive fabric4344505152, conductive rubber464748, and conductive liquid45. In these literatures, no complex array of stretchable electrodes needs to be fabricated within the entire sensing area.…”
mentioning
confidence: 99%